Novel insights into exhaustive exercise-induced myocardial injury: Focusing on mitochondrial quality control - Shi, Mingyue; Dong, Zhao; Zhao, Kai; He, Xiaole; Sun, Yang; Ren, Jun; Ge, Wei (Frontiers in Cardiovascular Medicine, 2022)
Regular moderate-intensity exercise elicits benefit cardiovascular health outcomes. However, exhaustive exercise (EE) triggers arrhythmia, heart failure, and sudden cardiac death. Therefore, a better understanding of unfavorable heart sequelae of EE is important. Various mechanisms have been postulated for EE-induced cardiac injury, among which mitochondrial dysfunction is considered the cardinal machinery for pathogenesis of various diseases. Mitochondrial quality control (MQC) is critical for clearance of long-lived or damaged mitochondria, regulation of energy metabolism and cell apoptosis, maintenance of cardiac homeostasis and alleviation of EE-induced injury. In this review, we will focus on MQC mechanisms and propose mitochondrial pathophysiological targets for the management of EE-induced myocardial injury. A thorough understanding of how MQC system functions in the maintenance of mitochondrial homeostasis will provide a feasible rationale for developing potential therapeutic interventions for EE-induced injury.